A biomechanical analysis of the relationship between tennis service motion and ball spin - Murata, M.; Fujii, N. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to investigate the relationship between the service motion and the ball spin. Ten male university tennis players were participated in this study. Three-dimensional coordinates data of the players performing flat, kick and slice services were collected using an 10-camera Vicon MX system. In a similar way, the three-dimensional coordinates data of the reflective markers on the ball were collected. The ball spin is controlled by swing direction of the racquet without changing swing speed. When players put a spin on the ball, they changed swing direction rightward to avoid a head-on collision of the ball and racquet. Moreover, the swing direction was mainly controlled by not change of arm swing motion but change of upper body posture.